2016
DOI: 10.3389/fimmu.2016.00458
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Dexamethasone and Monophosphoryl Lipid A Removes Disease-Associated Transcriptional Signatures in Monocyte-Derived Dendritic Cells from Rheumatoid Arthritis Patients and Confers Tolerogenic Features

Abstract: Tolerogenic dendritic cells (TolDCs) are promising tools for therapy of autoimmune diseases, such as rheumatoid arthritis (RA). Here, we characterize monocyte-derived TolDCs from RA patients modulated with dexamethasone and activated with monophosphoryl lipid A (MPLA), referred to as MPLA-tDCs, in terms of gene expression, phenotype, cytokine profile, migratory properties, and T cell-stimulatory capacity in order to explore their suitability for cellular therapy. MPLA-tDCs derived from RA patients displayed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
12
1
1
Order By: Relevance
“…Despite a recent study has shown no differences in HLA-DR expression in DCs obtained from Chilean RA-patients and HC 22 , our data here shows a strong exacerbation of HLA-DR density in DCs obtained from Chilean RA-patients in comparison to Chilean HC ( Figure 1A). This discrepancy could be due to the different sources of monocytes obtained to be differentiated into DCs: Whereas García-González obtained monocytes from leukopheresis from RA-patients and from buffy-coats from HC 22 , here we obtained monocytes from fresh blood samples from RA-patients and HC.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite a recent study has shown no differences in HLA-DR expression in DCs obtained from Chilean RA-patients and HC 22 , our data here shows a strong exacerbation of HLA-DR density in DCs obtained from Chilean RA-patients in comparison to Chilean HC ( Figure 1A). This discrepancy could be due to the different sources of monocytes obtained to be differentiated into DCs: Whereas García-González obtained monocytes from leukopheresis from RA-patients and from buffy-coats from HC 22 , here we obtained monocytes from fresh blood samples from RA-patients and HC.…”
Section: Discussioncontrasting
confidence: 99%
“…This discrepancy could be due to the different sources of monocytes obtained to be differentiated into DCs: Whereas García-González obtained monocytes from leukopheresis from RA-patients and from buffy-coats from HC 22 , here we obtained monocytes from fresh blood samples from RA-patients and HC. Since smoke has been proposed to represent one of the main environmental factors exacerbating disease manifestations and triggering RA 15,16 , we decided to analyse our results confined to the subgroup of smoker and non-smoker RA-patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All strategies lead to DCs with regulatory capacities, although some features may vary between protocols. Our group has described a protocol for tolDC generation from peripheral blood monocytes of healthy controls ( 20 ) and rheumatoid arthritis (RA) patients ( 21 ) using Dex to induce a tolerogenic phenotype and subsequent activation with the non-toxic lipopolysaccharide (LPS) analog monophosphoryl lipid A (MPLA) to confer lymph node homing capacity and stability. These cells, herein termed Dex-modulated and MPLA-activated DCs (DM-DCs), expressed low levels of CD83, CD86, and CD40, secreted high levels of IL-10 and TGF-β and low levels of IL-12, and stimulated T-cell proliferation and cytokine production at low levels in allogeneic and autologous cultures ( 20 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Согласно данным литературы, используемые в терапии РА препараты способ-ны индуцировать толерогенный потенциал ДК. В частности показано, что глюкокортикоиды угне-тают созревание генерируемых из моноцитов ДК [11,12,24]. Терапия больных РА моноклональ-ными антителами к TNF-α сопровождается ко-личественным снижением в циркуляции миелоид-ных и в меньшей степени плазмоцитоидных ДК и снижением ýкспрессии СD83 [25].…”
Section: Discussionunclassified